2014
DOI: 10.1111/desc.12191
|View full text |Cite
|
Sign up to set email alerts
|

Kin rejection: social signals, neural response and perceived distress during social exclusion

Abstract: Across species, kin bond together to promote survival. We sought to understand the dyadic effect of exclusion by kin (as opposed to non-kin strangers) on brain activity of the mother and her child and their subjective distress. To this end, we probed mother-child relationships with a computerized ball-toss game Cyberball. When excluded by one another, rather than by a stranger, both mothers and children exhibited a significantly pronounced frontal P2. Moreover, upon kin-rejection versus stranger-rejection, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 81 publications
(115 reference statements)
1
33
1
1
Order By: Relevance
“…It is therefore tempting to suggest that during this period, theta activity may tap into processes of expectancy violation, also associated with social exclusion (Somerville et al, 2006). By contrast, theta modulation at later processing stages is more closely linked to distress and anxiety, much like the frontal slow-wave activity that has been reported in several Cyberball studies (Crowley et al, 2010; Sreekrishnan et al, 2014; White et al, 2012). It is well established that increases in theta-band activity in humans are associated with experience of undesirable outcomes (Cohen et al, 2007), unpleasant experiences/events (Vecchiato et al, 2011), and/or negative affective states (Luu et al, 2000a).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…It is therefore tempting to suggest that during this period, theta activity may tap into processes of expectancy violation, also associated with social exclusion (Somerville et al, 2006). By contrast, theta modulation at later processing stages is more closely linked to distress and anxiety, much like the frontal slow-wave activity that has been reported in several Cyberball studies (Crowley et al, 2010; Sreekrishnan et al, 2014; White et al, 2012). It is well established that increases in theta-band activity in humans are associated with experience of undesirable outcomes (Cohen et al, 2007), unpleasant experiences/events (Vecchiato et al, 2011), and/or negative affective states (Luu et al, 2000a).…”
Section: Discussionmentioning
confidence: 59%
“…Functional magnetic resonance imaging (fMRI) and electroencephalogram (EEG) measures both show that various frontal responses are related to measures of distress, ostracism, mood, and attachment (Crowley et al, 2009; Crowley et al, 2010; Eisenberger et al, 2003; Masten et al, 2009; McPartland et al, 2011; Sreekrishnan et al, 2014; White et al, 2013; White et al, 2012). fMRI studies have identified a number of frontal regions engaged during social exclusion including the dorsal and ventral ACC, medial prefrontal cortex, ventro-lateral prefrontal cortex (Gunther-Moor et al, 2012), subgenual ACC (Masten et al, 2009; Masten et al, 2011), and right ventral prefrontal cortex (Eisenberger et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERPs have been used to probe real-time temporal brain activity during social ostracism in Cyberball (Crowley et al , 2009a,b, 2010; White et al , 2012, 2013; Sreekrishnan et al , 2014; Themanson et al , 2015). Previous ERP studies with Cyberball focused on frontal slow wave responses to exclusion events, with greater negative left frontal/central slow waves tracking greater experienced ostracism distress (Crowley et al , 2009a,b, 2010; White et al , 2013; Sreekrishnan et al , 2014).…”
Section: Social Exclusionmentioning
confidence: 99%
“…Building on this work, one study reported that the level of dismissing attachment in an early adolescent sample was associated with the ERP response to social exclusion by unfamiliar peers (White et al, 2012). Further adaptation of this paradigm to examining the neural correlates of rejection by mother and child has recently been advanced (Sreekrishnan et al, 2014). A natural extension of this work would be to examine the attachment style of mothers and their children and how the quality of dyadic relationships influences the response both to infant cues and to similar social exclusion paradigms (e.g., Fraedrich, Lakatos, & Spangler, 2010).…”
Section: Summary and Future Directionsmentioning
confidence: 99%